Human Cytomegalovirus Interleukin-10 Downregulates Metalloproteinase Activity and Impairs Endothelial Cell Migration and Placental Cytotrophoblast Invasiveness In Vitro - Yamamoto-Tabata, Takako (American Society for Microbiology, 2004)
At the uterine-placental interface, fetal cytotrophoblasts invade the decidua, breach maternal blood vessels, and form heterotypic contacts with uterine microvascular endothelial cells. In early gestation, differentiating- invading cytotrophoblasts produce high levels of matrix metalloproteinase 9 (MMP-9), which degrades the extracellular matrix and increases the invasion depth. By midgestation, when invasion is complete, MMP levels are reduced. Cytotrophoblasts also produce human interleukin-10 (hIL-10), a pleiotropic cytokine that modulates immune responses, helping to protect the fetal hemiallograft from rejection. Human cytomegalovirus (CMV) is often detected at the uterine-placental interface. CMV infection impairs cytotrophoblast differentiation and invasion, altering the expression of the cell adhesion and immune molecules. Here we report that infection with a clinical CMV strain, VR1814, but not a laboratory strain, AD169, downregulates MMP activity in uterine microvascular endothelial cells and differentiating-invading cytotrophoblasts. Infected cytotrophoblasts expressed CMV IL-10 (cmvIL-10) mRNA and secreted the viral cytokine, which upregulated hIL-10. Functional analyses showed that cmvIL-10 treatment impaired migration in endothelial cell wounding assays and cytotrophoblast invasion of Matrigel in vitro. Comparable changes occurred in cells that were exposed to recombinant hIL-10 or cmvIL-10. Our results show that cmvIL-10 decreases MMP activity and dysregulates the cell-cell and/or cell-matrix interactions of infected cytotrophoblasts and endothelial cells. Reduced MMP activity early in placental development could impair cytotrophoblast remodeling of the uterine vasculature and eventually restrict fetal growth in affected pregnancies.